Crecimiento longitudinal del alcornoque: segmentos y hojas (SCIENTIA gerundensis, 1988)
This paper is directed to the basic understand of longitudinal growth of the cork-tree Quercus suber L. Branch constitution is analized through the relation of segments and leaves. To duly recognize segments in branches, an apropiate nomenclature is used. Segments length changes from 0,2 to 11,6 cm, with an average of 2,3 cm. Two kind of shoots, long and short shoots, can be distinguished. Segment elongation tend to decrease as succesive periods accumulate. No differences in segments can be related to the period of the year in which they were developed. Leaves show heteroblastic distribution. Leave lamina has an average length of 3,3 cm and is 2,O cm wide. Petiol is very constant with an average of 0,6 cm.